2018
DOI: 10.1371/journal.pone.0190990
|View full text |Cite
|
Sign up to set email alerts
|

The "Tracked Roaming Transect" and distance sampling methods increase the efficiency of underwater visual censuses

Abstract: Underwater visual census (UVC) is the most common approach for estimating diversity, abundance and size of reef fishes in shallow and clear waters. Abundance estimation through UVC is particularly problematic in species occurring at low densities and/or highly aggregated because of their high variability at both spatial and temporal scales. The statistical power of experiments involving UVC techniques may be increased by augmenting the number of replicates or the area surveyed. In this work we present and test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…Most underwater visual census (UVC) fish transects use survey distances of 25–150 m. With the apparent rarity of Napoleon fish (there can be fewer than 1 fish km −1 of transect survey), these lengths were deemed inappropriate (e.g. Irigoyen et al, ). Instead, the sampling strategy involved long snorkelling transects (several kilometres in length) along specific features of adult habitat, such as the reef shelf edge, that are identifiable in satellite or aerial images and easy to follow (Oddone et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most underwater visual census (UVC) fish transects use survey distances of 25–150 m. With the apparent rarity of Napoleon fish (there can be fewer than 1 fish km −1 of transect survey), these lengths were deemed inappropriate (e.g. Irigoyen et al, ). Instead, the sampling strategy involved long snorkelling transects (several kilometres in length) along specific features of adult habitat, such as the reef shelf edge, that are identifiable in satellite or aerial images and easy to follow (Oddone et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Global Positioning System (GPS) to quantify their abundance and sizes, and to allow future reassessments of the same areas. Most underwater visual census (UVC) fish transects use survey distances of 25-150 m. With the apparent rarity of Napoleon fish (there can be fewer than 1 fish km −1 of transect survey), these lengths were deemed inappropriate (e.g Irigoyen et al, 2018)…”
mentioning
confidence: 99%
“…Other recent studies have examined and/or compared the performance of various UVS methods ( Bosch et al, 2017 ; Irigoyen et al, 2018 ). Bosch et al (2017) compared the output of three different methods for studying fish assemblages, UVC (strip transects of fixed length and width), Fish Traps, and Baited Cameras.…”
Section: Introductionmentioning
confidence: 99%
“…The authors mainly focused on species diversity; they did not assess the performance of the methods to estimate species absolute or relative abundance. Irigoyen et al (2018) used conventional strip transects of various fixed width and the distance sampling technique in combination with the “Tracked Roaming Diver” technique (a sampling method that maximizes the length of the transect and thus the area studied). They proposed that the combination of the two latter methods provides a more efficient way for UVS.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, 399 Einsing et al (1995) showed that distance sampling, compared to quadrat sampling and strip 400 transects, produced density estimates that were closer to true densities, while Thresher and Gunn 401 (1986) proposed that distance sampling should be preferred for the assessment of secretive 402 species. Irigoyen et al (2018) also proposed the distance sampling as an appropriate method to 403 survey medium-and large-sized fish species, although they also discussed some disadvantages of 404 the specific method that should be taken into consideration. Best fit model, maximum width of line transect after truncation (w) and value of detectability (Pa) of the DISTANCE analysis for each species.…”
Section: These S Luridus S Salpa O Melanura and D Vulgaris S mentioning
confidence: 99%